2020
DOI: 10.12740/pp/onlinefirst/99164
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of eating disorders among upper secondary school female students

Abstract: Cel pracyBadania nad rozpowszechnieniem występowania zaburzeń odżywiania nie były często podejmowane w ostatnich latach ani w Polsce, ani w skali świata. Trudno również oszacować rozpowszechnienie tych zaburzeń. Celem pracy była ocena rozpowszechnienia występowania zaburzeń odżywania w grupie polskich uczennic szkół ponadgminazjalnych z uwzględnieniem typu szkoły oraz warunków mieszkaniowychMetodaBadania zaburzeń odżywiania przeprowadzono w okresie 03 – 06 2017 r., wśród uczennic szczecińskich szkół ponadgimna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Analysis of the source literature confirms the continual increase of the number of people suffering from eating disorders worldwide [1,2]. Epidemiological data confirm the increasing importance of the problem in European countries [3,4], including Poland [5,6], the United States of America [7], Latin America [8], Arab countries [9,10], Africa [11], and Asia [12][13][14][15][16], with the risk of development of eating disorders being especially high in Japan [17]. The Global Burden of Disease (GBD) study from 2015 [18] confirmed the steady increase of eating disorders in women all around the world [19].…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 65%
See 2 more Smart Citations
“…Analysis of the source literature confirms the continual increase of the number of people suffering from eating disorders worldwide [1,2]. Epidemiological data confirm the increasing importance of the problem in European countries [3,4], including Poland [5,6], the United States of America [7], Latin America [8], Arab countries [9,10], Africa [11], and Asia [12][13][14][15][16], with the risk of development of eating disorders being especially high in Japan [17]. The Global Burden of Disease (GBD) study from 2015 [18] confirmed the steady increase of eating disorders in women all around the world [19].…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 65%
“…However, some papers provide results indicating the existence of a significant relation between dissatisfaction with body image and excessive pursuit of thinness and restrictive attitudes towards nutrition and the body (unhealthy and inappropriate for one's BMI) evidenced by Japanese women [25,77]. It is worth mentioning that the similar restrictive tendencies and the presence of the correlation between them and body dissatisfaction are also observed in the population of young Polish women [5,78]. On the other hand, recent articles present less data on bulimic tendencies in the population of young Japanese women.…”
Section: Similarities and Differences Between Polish And Japanese Womenmentioning
confidence: 96%
See 1 more Smart Citation
“…There is a significantly lower frequency of eating disorders in the population of men compared to women (55,56). In addition, factors explaining the incidence of eating disorders mention that the mass media has a larger influence on girls and women, because they show higher level of internalization of cultural standards of body image and physical appearance than men (24,(57)(58)(59). Due to the abovementioned reasons, respondents were divided by gender (similar ages and BMI).…”
Section: The Current Studymentioning
confidence: 99%
“…While recent research on the eating disorder has reported stability in the incidence of anorexia and decreased bulimia [47,48], there is a notable increase in the obesity levels of children under 12. The Ministry of Health and Consumer Affairs has been providing data since 2006 and the World Health Organization (WHO) [49] estimates that child obesity is around 14%, indicating that overweight is over 12% and it also coined in 2001 the term "Globesity" to define the severity of the obesity pandemic in the world.…”
Section: About the Influence Of The Media On Food-related Diseasesmentioning
confidence: 99%